(untitled) (Research, Society and Development, 2020)
Objective: to describe the profile and evaluate the quality of life of people living with HIV treated in public health services in the city of Rio de Janeiro. Method: a descriptive, quantitative study with 180 people living with HIV in three Specialized Care Services (SAE). A questionnaire of socioeconomic and clinical data and the instrument for assessing quality of life (WHOQOL-HIV bref) were used. The data were organized by the SPSS software. Results: the domain spirituality, religion and beliefs people had the highest score, followed by the psychological domain. The lowest averages were in the domains level of independence and environment, which are related to the need for treatment and the low socioeconomic level, reflecting negatively on the quality of life of the group. Conclusion: it was found in the general analysis that there is a predominantly positive assessment among the members of the group, evidenced both in the self-assessment and as a result of the analysis of the scores of the WHOQOL-HIV brief domains.